Strategi Bertahan Hidup dalam Pemenuhan Kebutuhan Ekonomi Keluarga Suku Bajo di Daratan Tanete Riattang Timur Kabupaten Bone - Ramli Umar; Erman Syarif (Seminar Nasional LP2M UNM, 2019)
The purpose of this study is; (1) Knowing the factors that affect the Bajo Tribe move from sea to the mainland of the Tanete Riattang Timur Bone Regency; (2) Knowing the survival strategy of the Bajo people living on the mainland of Tanete Riattang Timur Bone Regency. This research was carried out in Bone regency Tanete Riattang Timur district Bajoe village precisely in the Bajo tribe. This type of research is qualitative using case studies. The technique of collecting data is done through observation, interviews, literature review and documentation. The informants of this study are customary leaders, Bajo tribe people, Bajoe village heads, Bajo ward heads, non-Bajo tribes who live in the Bajo environment. The Bajo people who will be interviewed are chosen randomly and the number of informants is determined according to the needs of the researchers, as well as the non-Bajo people. The results of research that has been carried out concerning the survival strategy of the Bajo Tribe in the mainland of Tanete Riattang Timur Bone Regency shows that (1) Bajo people in the mainland occupy the Bajo Environment area on the basis of the local government by providing land and property rights certificates. They also feel comfortable with the life they are living in by living on land but their daily activities remain at sea. (2) The survival strategy still relies on income as a fisherman and there are a number of side jobs such as farming, gardening, or as carpenters. Another thing that is also done by selling possessions or borrowing from relatives to fulfill their life needs is also those who open small businesses at home for women such as opening small substations or salons to increase their income to meet their daily needs.